Transcranial Magnetic Mapping of the Short-Latency Modulations of Corticospinal Activity from the Ipsilateral Hemisphere during Rest - Cattaneo, Luigi; Barchiesi, Guido (Frontiers in Neural Circuits, 2011)
Skilled hand function relies heavily on the integrity of the primary motor cortex (M1) and on a web of cortico-cortical connections projecting onto it. We used a novel explorative paradigm to map the origin of cortico-M1 pathways assessed by dual transcranial magnetic stimulation (TMS) in 3 healthy participants. Subthreshold conditioning TMS (cTMS) was delivered over a grid of » 100 spots. covering the left hemisphere, and was followed by suprathreshold test stimuli (tTMS) delivered over the ipsilateral M1. Grid points were tested 8 times, with inter-stimulus intervals between cTMS and tTMS of 4 and 7 ms. Participants were asked to stay relaxed with no particular task. Motor evoked potentials (MEPs) from cTMS+tTMS were normalized to MEPs from tTMS alone and were compared to the value expected from tTMS alone using t-statistics. The t-values from each grid point were then used to plot statistical maps. Several foci of significant cortico-M1 interactions were found in the dorsal-medial frontal cortex, in the ventral frontal cortex, in the superior and inferior parietal lobules and in the parietal operculum. The majority of active foci had inhibitory effects on corticospinal excitability. The spatial location of the network of different subjects overlapped but with some anatomical variation of single foci. TMS statistical mapping during the resting state revealed a complex inhibitory cortical network. The explorative approach to TMS as a brain mapping tool produced results that are self-standing in single subjects overcoming inter-individual variability of cortical active sites.